MU’ALLIM AL-LUGHAH AL-‘ARABIYAH FÎ DHAU AL-TSAURAH AL-SHINÂ’IYAH AL-RÂBI’AH: TAHADIYÂTUHU WA MATHÂLIBUHU - Haris, Abdul (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
This study aims to describe the challenges of Arabic teachers in the context of the industrial revolution 4.0 and their demands in facing these challenges. The study used a qualitative approach with 20 Arabic teachers as respondents. In this study the data were collected by using questionnaires and interviews. To analyze the data, the researcher used the interactive technique of Miles and Huberman, while to test the validity of the data, the method of triangulation technique was used. The research showed that the Industrial Revolution 4.0 created various challenges for Arabic language teachers. These challenges are around the ability to cope with technology and the development of technology-based media and methods, the diverse conditions of students in learning the Arabic language, the poor condition of the Arabic language in some academic institutions, and the faith. These challenges require Arabic language teachers to master technology, develop their methodological competence, be creative and innovative, and upgrade the ability to cooperate with others, carry out scientific research, and strengthen the faith.